Grid integration and coordinated control of voltage source inverters with energy storage systems - Qi, Yang (Nanyang Technological University, 2021)
Recent advances in power-electronics technologies facilitate the integration of distributed generations (DGs), such as renewable energy resources (RESs) and distributed energy storage systems (DESSs). The “microgrid” concept is formed when a number of DGs and loads are coupled together through power electronics converters. To maintain the power balance of a microgrid and perform the grid-forming function, DESSs should be properly controlled through the interfaced power converters. This thesis aims to analyze and overcome several issues regarding the coordination and control of DESSs, with the focus on the following aspects: fundamental power sharing among DESSs, unbalanced power sharing among DESSs, harmonic power sharing among DESSs, and the synchronization stability of Voltage source inverter (VSI) with DESSs. The detailed descriptions will be respectively provided hereinafter. In an islanded AC microgrid, DESSs are usually integrated to the microgrid through voltage source inverters (VSIs). To improve the operation efficiency and avoid the undesired overloading, it is expected that multiple VSIs, which operate in parallel with each other, can share active and reactive power according to their power ratings. Though the active power can always be accurately shared by the frequency droop control, it is difficult to achieve the reactive power sharing as desired due to mismatched grid impedances and voltage sensor scaling errors. To address this problem, a decentralized reactive power control scheme is proposed through the inherent pulse-width modulation (PWM) dead-time effect. More specifically, a supplementary control is incorporated into the voltage control loop, which utilizes the dead-time effect to equalize the power factors of all the VSIs. As a consequence, the reactive power sharing can be accurately shared in a fully decentralized manner. Finally, simulation and experimental results are provided for verification. In addition to the reactive power sharing, the unbalanced power introduced by negative-sequence load currents should also be accurately shared among DESSs based on the power ratings of VSIs. It is revealed that even small voltage measurement scaling errors may deteriorate the power sharing accuracy by injecting positive- and negative-sequence circulating currents. Such a negative impact cannot be avoided given that the voltage-feedback control is well designed to have excellent tracking ability. To address this problem, a hybrid feedback and feedforward impedance-shaping control is developed, which makes the power-sharing performance robust against voltage measurement errors. The feedforward control is implemented to reshape the VSI impedances at the fundamental frequency such that the reactive and unbalanced power-sharing performance can be ensured. Meanwhile, conventional voltage-feedback control is also implemented to compensate for voltage distortions and improve the harmonic power-sharing performance. Since no communications and prior sensor error knowledge are required, the proposed control algorithm provides a simple but effective solution for decentralized power sharing among parallel three-phase VSIs. Finally, both simulation and experimental results are provided to verify the effectiveness of the proposed control strategy. Due to the proliferation of nonlinear loads, considerable harmonic currents are injected into the microgrid, leading to severe power quality issues. In view of this challenge, it is expected that DESSs can cooperatively share the harmonic currents and contribute to the total harmonic distortion (THD) reduction of the point of common coupling (PCC) voltage. It is widely accepted that the harmonic currents of nonlinear loads are distributed among parallel VSIs according to their effective harmonic impedances, i.e., the sums of VSI impedances and grid impedances. Since grid impedances are unknown and could be mismatched, the VSI output impedance should be reshaped to improve the harmonic power-sharing accuracy. However, as conventional techniques only regulate VSI output impedances in one dimension, only one degree of freedom (DOF) is provided for the impedance shaping. It is found that such measures can hardly fulfill the proper harmonic power-sharing requirement under complex grid impedance situations. As a result, circulating harmonic currents will occur and produce additional power losses even if the harmonic power has been accurately shared. To solve this problem, a two-dimensional impedance-shaping control is developed, which can adaptively regulate VSI output resistances and inductances at the same time. The proposed control strategy requires no prior grid impedance knowledge and can eliminate the circulating harmonic currents for arbitrary grid impedances, as verified by experimental results. Another important aspect related to the VSI operation is the synchronization stability, which is not only influenced by VSI control parameters but also affected by grid structure, feeder impedances, and etc. Seen from the perspective of a local VSI, it is difficult to obtain the complete grid information. As a consequence, unpredicted low-frequency angle oscillations and even loss of synchronization may occur and pose a significant threat to the system. To overcome this issue, a design-oriented analysis is proposed for grid-connected VSIs. To be specific, by comparing the frequency-power characteristic (FPC) of the VSI and that of the power grid, clear insights are gained into the synchronization dynamics. Moreover, a frequency response identification (FRI) approach is further proposed to acquire the grid FPC without requiring grid information. Through this effort, low-frequency oscillations can be easily identified and damped through reshaping the FPC of VSI. Finally, the experimental results of a grid-connected VSI are provided for verification. In summary, the overall research problem of this thesis is load power sharing and stability analysis of VSIs with the distributed energy storage system. This thesis analyzes the reasons for inaccurate power sharing and proposes control schemes that can improve the active, reactive, unbalanced, and harmonic power sharing in decentralized or distributed manners. Besides, the synchronization stability has also been studied and analyzed.